Prevalence and Characterization of Some Pathogenic Bacteria in Fermented Milk Products and Mish Cheese in Dakahalia Governorate, Egypt - Abd Elkader Mahmoud Abd El latif, Rana; El Sherbini El-sayed Ali, Mohammed; Abdelkhalek, Adel (Journal of Advanced Veterinary Research, 2022)
Bacterial contamination of fermented dairy products has serious implications for both safeties of the final products, and the transmission of foodborne pathogens to the consumers. In this regard, 175 samples of fermented dairy products including 50 each of plain yoghurt, fruit yoghurt, laban rayeb, and 25 from mish cheese were randomly collected from different supermarkets and retail shops in Dakahlia Governorate, Egypt. Samples were examined bacteriologically for the prevalence of Staphylococcus aureus (S. aureus), Escherichia coli (E. coli), particularly, E. coli O157. The recovered isolates were examined for the detection of toxin, and virulence-associated genes using PCR. The obtained results showed that the average counts (CFU/g) of total bacterial, psychrotrophic, coliform, and S. aureus were 1.72x105, 9.9 x103, 5.08x102, and 3.07 x102 for the plain yoghurt, 7.1 x 104, 2.3 x 103, 9.5 x10, and 3.3 x10 for fruit yoghurt, 6.07x104, 6.1 x 103, 9.8 x10, and 1.35x102 for laban rayeb, Â and 1.2 x 106, 2.5 x104, 8.3 x10, and 7.2 x103 for Mish cheese, respectively. E. coli and E. coli O157 were detected in 13 out of 175 (7.43%) and 4 out of 175 (2.3%) samples, respectively. Using PCR for 9 selected E. coli isolates showed that 7 out of 9 E. coli isolates were positive for the stx1 gene, 5 out of 9 were positive for stx2, and 3 out of 9 were positive for eaeA, and 4 out of 9 were positive for hylA. S. aureus showed that 55.6% of the recovered isolates were coagulase positive. Ten randomly selected S. aureus isolates tested positive for nuc (thermonuclease genes), while mecA (methicillin-resistant S. aureus â€œMRSAâ€) gene was detected in 20% of the examined isolates. Therefore, strict hygienic measures should be adopted during all steps of the manufacture of such dairy products.